Philosophy of science and the diagnostic process. - Willis, B; Beebee, H; Lasserson, D (2013)
This is an overview of the principles that underpin philosophy of science and how they may provide a framework for the diagnostic process. Although philosophy dates back to antiquity, it is only more recently that philosophers have begun to enunciate the scientific method. Since Aristotle formulated deduction, other modes of reasoning including induction, inference to best explanation, falsificationism, theory-laden observations and Bayesian inference have emerged. Thus, rather than representing a single overriding dogma, the scientific method is a toolkit of ideas and principles of reasoning. Here we demonstrate that the diagnostic process is an example of science in action and is therefore subject to the principles encompassed by the scientific method. Although a number of the different forms of reasoning are used readily by clinicians in practice, without a clear understanding of their pitfalls and the assumptions on which they are based, it leaves doctors open to diagnostic error. We conclude by providing a case example from the medico-legal literature in which diagnostic errors were made, to illustrate how applying the scientific method may mitigate the chance for diagnostic error.